Chemical Bonding in Transition Metal Nitride Os3N3 + Cluster: 6π Inorganic Benzene and δ2δ1δ1 Aromaticity - Liu, Na; You, Xue-Rui; Zhai, Hua-Jin (ACS omega, 2018)
Inorganic benzene-like clusters with a planar hexagonal ring are of interest in chemistry, as are new types of aromaticity, multifold aromaticity, and in particular δ aromaticity beyond carbon-based organic systems. Here we report on a computational study of chemical bonding in a binary Os3N3 + D 3h (7A2″) cluster. This transition metal nitride cluster assumes a perfectly planar, heteroatomic, hexagonal geometry. An array of quantum chemistry tools is exploited to elucidate the electronic, structural, and bonding properties of D 3h Os3N3 + cluster, which include canonical molecular orbitals, adaptive natural density partitioning, natural bond orbital analysis, orbital composition calculations, and nucleus-independent chemical shifts. The computational data collectively support the bonding picture of 2-fold π/δ aromaticity: 6π electrons delocalized over all Os/N centers versus an Os-based 4δ framework in the unique δ2δ*1δ*1 configuration. The π sextet renders this heteroatomic cluster an inorganic analog of benzene. Transition metal-based inorganic benzenes are unknown in the literature, to our knowledge. The triplet 4δ electron-counting is a rare case of d-orbital aromaticity and δ-aromaticity, following the reversed 4n Hückel rule for aromaticity in a triplet system. This bonding picture is concrete, differing fundamentally from a recent study on the relevant system.